Vitiligo Treatment Impact score (VITs): development and validation of a vitiligo burden of treatment questionnaire using the ComPaRe Vitiligo e‐cohort. (12th November 2021) - Shourick, J.; Seneschal, J.; Andreu, N.; Meurant, J.‐M.; Pane, I.; Ravaud, P.; Tran, V.‐T.; Ezzedine, K.
Abstract: Background: Vitiligo management is challenging and requires long‐term adherence of patients who often complain of the burden associated with treatment. Objective: To develop and validate a patient reported measurement of the burden of treatment in vitiligo. Methods: The study was nested within the ComPaRe Vitiligo e‐cohort, an online e‐cohort of vitiligo patients in France. Items were derived from a literature review and from the qualitative analysis of a survey using open‐ended questions of 204 patients with Vitiligo. Construct validity of the resulting instrument was assessed by comparing the instrument's score to the Dermatology Life Quality Index (DLQI), Vitiligo Impact Patient score (VIPs) and Treatment Burden Questionnaire (TBQ) scores. Reliability was assessed by test‐retest with 15 ± 10 days of interval between both assessments. Results: In total, 343 adult participants participated in the validation of the Vitiligo Treatment Impact score (VITs). The VITs is a 19‐item questionnaire assessing the burden of treatment in patients with vitiligo with results suggesting four domains ('Finding a doctor', 'Phototherapy', 'Topical treatment' and 'Impact on outdoor activities and photoprotection'). The VITs total score was well correlated with the DLQI, VIP and TBQ scores. Agreement between test and retest was good (ICC 0.705, 95% CI 0.491–0.818). Conclusions: We developed a patient reported measurement of the burden of treatment in vitiligo with good psychometric properties.